Prevalence and Determinants of Unintended Pregnancy Among Mothers Delivered in Tertiary and General hospitals, Tigray Region, Ethiopia - Ataklti Shiferaw; Amanuel Gessessew; Girmatsion Fisseha; Hale Teka; Sumeya Ahmed; Jessica Morgan; Gelila Goba; Yemane, Awol (Ethiopian Journal of Reproductive Health, 2023)
Background: Unintended pregnancy represents an important public health challenge in many countries, especially in the developing world. Numerous prevention strategies have been employed worldwide in an effort to address this problem. Unintended pregnancies contribute significantly to adverse health, social and economic outcomes and increase the risks of maternal death as well as neonatal, infant and child mortality. At present, standardized efforts to reduce the incidence of unintended pregnancy are sparse. Objective: This study aimed to assess prevalence and determinants unintended pregnancy among mothers delivered in Ayder Comprehensive Specialized Hospital and Mekelle hospital. Methods: A facility based cross-sectional study was conducted over a period of two months (January 1, 2018 to February 30, 2018). The study was conducted in among 614 postpartum mothers across two hospital sites during the aforementioned time period. Bivariate logistic regression was used to assess for association between the independent variables and unintended pregnancy. Statistical significance was determined as P < 0.05. Results: A totals of 614 mothers participated in the study. The prevalence of unintended pregnancy was 42.8%. Mistimed pregnancy accounting for 33.7 % and unwanted pregnancy accounting for 9.1%. About 88 % of mistimed pregnancies were due to contraception not used and 12% are due to contraception failure. Lower level of education, interpregnancy interval of 6 months to 5 years, older maternal age, and larger family size were factors significantly associated with unintended pregnancy. Conclusions: Nearly half of women had an unintended pregnancy, a rate higher than previously reported. Lower level of education, older maternal age, and larger family were factors significantly associated with unintended pregnancy. The high prevalence of unintended pregnancies in Mekelle highlights the need for implementation strategies that encourage education of women, creating awareness on family planning and child spacing.